Policy coherence analysis in climate-smart agriculture (CSA) in Africa - Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Through this policy coherence analysis and the recommendations thereof, AICCRA aims to identify and address critical gaps in the design, implementation, monitoring and financing of climate and agricultural policies throughout Africa. Enhanced policy coherence will promote the integration of climate and agricultural agendas; foster alignment across local, national and international actions; overcome fragmented or siloed policy actions; and ultimately support impactful policy actions that are aligned with meeting global resilience outcomes.